2006
DOI: 10.1038/sj.onc.1209690
|View full text |Cite
|
Sign up to set email alerts
|

Identification of target genes in laryngeal squamous cell carcinoma by high-resolution copy number and gene expression microarray analyses

Abstract: Molecular mechanisms contributing to initiation and progression of head and neck squamous cell carcinoma are still poorly known. Numerous genetic alterations have been described, but molecular consequences of such alterations in most cases remain unclear. Here, we performed an integrated high-resolution microarray analysis of gene copy number and expression in 20 laryngeal cancer cell lines and primary tumors. Our aim was to identify genetic alterations that play a key role in disease pathogenesis and pinpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 37 publications
9
77
0
1
Order By: Relevance
“…In agreement with our findings, very recently, Järvinen et al (32) proposed that FADD and PPFIA1 are likely candidates, implicating that these two genes are located near the core of the amplicon. However, our comprehensive analysis of all genes in the 11q13 region revealed that, in addition to FADD and PPFIA1, six other likely candidate genes (TPCN2, CCND1, FLJ42258, ORAOV1, FGF19, and CTTN) within the 11q13.3 CRA are coamplified in at least 25 of 29 cases and show a strong correlation between expression and amplification (Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with our findings, very recently, Järvinen et al (32) proposed that FADD and PPFIA1 are likely candidates, implicating that these two genes are located near the core of the amplicon. However, our comprehensive analysis of all genes in the 11q13 region revealed that, in addition to FADD and PPFIA1, six other likely candidate genes (TPCN2, CCND1, FLJ42258, ORAOV1, FGF19, and CTTN) within the 11q13.3 CRA are coamplified in at least 25 of 29 cases and show a strong correlation between expression and amplification (Table 1).…”
Section: Discussionsupporting
confidence: 81%
“…We have recently shown that liprin-a1 is an essential regulator of cell spreading on extracellular matrix (ECM) (Asperti et al, 2009(Asperti et al, , 2010. Interestingly, the gene for liprin-a1 is included in the human chromosomal region 11q13 (Katoh and Katoh, 2005;Ja¨rvinen et al, 2006) that is frequently amplified in various malignant tumors, including B20% of breast cancers (Al-Kuraya et al, 2004). Based on this information, we have addressed the role of liprin-a1 in the regulation of the different cellular processes required for the invasion of the MDA-MB-231 breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The cell lines were previously characterized. 4,5 Cells were grown in adhesive 25 cm 2 flasks in standard Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum at 37°C under 5% CO 2 atmosphere. Cells were harvested at a confluence of 70%-90%.…”
Section: Lscc Cell Lines Primary Tumors and The Control Samplesmentioning
confidence: 99%